Mouse fibroblast (type I) and immune (type II) interferons: pronounced differences in affinity for gangliosides and in antiviral and antigrowth effects on mouse leukemia L-1210R cells. - Ankel, H (Proc Natl Acad Sci U S A, 1980)
Different interferons can be obtained from the same animal species depending on the cells and (or) the inducers used. Interferons of type I and type II differ not only antigenically but also in molecular weight and stability at low pH. We have investigated whether mouse type I and type II interferons also differ in properties relating to their biological action. We present evidence which suggests that the molecular mechanism leading to antiviral and antigrowth effects induced by both types of interferon in susceptible cells must differ in at least one important step. Antiviral and antigrowth activities of type I but not of type II interferon are both inhibited when gangliosides are added to cell cultures together with the interferon. Whereas type I interferon strongly binds to ganglioside affinity columns and can be eluted with solutions of N-acetylneuraminyllactose, type II interferon passes through such columns unretarded. L-1210 mouse leukemia cells (L-1210S) respond equally well to antiviral and antigrowth activities of type I and type II interferons. Type I interferon-resistant L-1210 cells (L-1210R), derived from L-1210S cells after continuous culture in the presence of mouse fibroblast interferon, lack antiviral and antigrowth response to mouse type I interferon [Gresser, I., Bandu, H.T. & Brouty-Boyé, D. (1974) J. Natl. Cancer Inst. 52, 553-559]. However, these cells display the same sensitivity toward type II interferon as do the parent L-1210S cells from which they were derived and respond equally well to its antiviral and antigrowth activities. IMAGES: